Aplikasi Drone Militer Dengan Produk Alutsista Indonesia untuk Over the Horizon Operations - Denny Lesmana; Yudha Permana; Budi Santoso; Ardian Infantono (Akademi Angkatan Udara, 2021)
Drones/unmanned aircraft are one of the technologies in the defense sector that are included in the Indonesian government's strategic program. In the era of Information technology and society 5.0, the use of high technology is indispensable in overcoming various problems, especially Indonesia which has a large area. Drones can be a multifunctional platform that can play a role in War Military Operations (OMP) and Military Operations Other Than War (OMSP). The use of drones in the military is generally used as part of